Genomic and biochemical comparison of allelic triple‐mutant lines derived from conventional breeding and multiplex gene editing - Junqi Liu; Ritesh Kumar; Samatha Gunapati; Steven Mulkey; Yinjie Qiu; Yer Xiong; Vishnu Ramasubramanian; Jean‐Michel Michno; Praveen Awasthi; Daniel D. Gallaher; Thi Thao Nguyen; Won‐Seok Kim; et al. (The Plant Genome, 2025)
Abstract Multiplex gene editing allows for the simultaneous targeting and mutagenesis of multiple loci in a genome. This tool is particularly valuable for plant genetic improvement, as plant genomes often require mutations at multiple loci to confer useful and/or novel traits. However, the regulation of gene editing can vary depending on the number of loci targeted. In this study, we developed triple‐mutant soybean (Glycine max (L.) Merrill) lines using different crop improvement strategies, including conventional backcross breeding of standing variant alleles and clustered regularly interspaced short palindromic repeats‐based multiplex editing to introduce new alleles. The mutations were targeted to genes encoding seed antinutritional components, as previously described in a triple null soybean carrying knockout alleles for a Kunitz trypsin inhibitor, a soybean agglutinin, and the allergen P34 protein. The products developed from these respective genetic improvement pipelines were tested for differences between the triple‐mutant lines and their parental lines. Analyses included genomics, seed proteomics, trypsin inhibition, seed protein digestibility, and harvestable yield of the different lines. We observed that both multiplex gene editing and conventional breeding approaches produced essentially equivalent products in comparison to their parental lines. We conclude that the multiplex gene editing strategy is not inherently riskier than conventional breeding for developing complex mutant lines of this type.